1999
DOI: 10.1046/j.1365-2605.1999.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species influence the acrosome reaction but not acrosin activity in human spermatozoa

Abstract: It is now widely accepted that the higher levels of reactive oxygen species (ROS) produced by damaged or deficient spermatozoa are associated with a loss of motility and a decreased capacity for sperm-oocyte fusion. Furthermore, earlier studies show, under physiological conditions, that some ROS may be involved in capacitation and hyperactivation of human spermatozoa. We measured ROS levels, acrosome reaction (AR) and acrosin activity (AA) in semen samples from suspected subfertile men to reveal the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…Oxidative stress has been suggested as one of the major cellular mechanisms involved in male infertility [105]. Oxidative stress affects the sperm membrane through lipid peroxidation [106], leading to loss of membrane stability and selective permeability, which, in turn, can cause mitochondrial dysfunctions [81], defective acrosome reaction [107], and sperm DNA fragmentation [108]. Hence, our results clearly show that viable sperm from an ejaculate of lower quality possesses protective mechanisms against the effects of the surrounding oxidative stress.…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupmentioning
confidence: 59%
“…Oxidative stress has been suggested as one of the major cellular mechanisms involved in male infertility [105]. Oxidative stress affects the sperm membrane through lipid peroxidation [106], leading to loss of membrane stability and selective permeability, which, in turn, can cause mitochondrial dysfunctions [81], defective acrosome reaction [107], and sperm DNA fragmentation [108]. Hence, our results clearly show that viable sperm from an ejaculate of lower quality possesses protective mechanisms against the effects of the surrounding oxidative stress.…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupmentioning
confidence: 59%
“…Ichikawa et al [83] compared the effect of small amounts of free radicals in stimulating the exocytosis and activation of acrosin. Samples were collected from normozoospermic and oligozoospermic patients.…”
Section: Acrosome Reactionmentioning
confidence: 99%
“…Superoxide anion (O 2 -·) and hydrogen peroxide (H 2 O 2 ) are the common forms of ROS. Some studies suggested that relatively low concentrations of ROS are beneficial for the normal functions of sperm capacitation [4], but excessively high concentrations of ROS are associated with lower acrosin activity [5], sperm DNA fragmentation, impaired sperm motility [6,7], decrease in sperm acrosome reaction and fusiogenic ability [8]. Clinical studies showed that oral antioxidant treatment appeared to improve sperm DNA integrity and outcomes of in vitro fertilization with intracytoplasmic sperm injection among patients with sperm DNA damage or other male infertility [9,10].…”
Section: Introductionmentioning
confidence: 99%